2016
DOI: 10.1016/j.ajog.2015.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Cervical phosphorylated insulin-like growth factor binding protein-1 test for the prediction of preterm birth: a systematic review and metaanalysis

Abstract: OBJECTIVE To assess the accuracy of the cervical phosphorylated insulin-like growth factor binding protein-1 (phIGFBP-1) test to predict preterm birth in women with and without symptoms of preterm labor through use of formal methods for systematic reviews and meta-analytic techniques. DATA SOURCES PubMed, Embase, Cinahl, Lilacs, and Medion (all from inception to June 20, 2015), reference lists, conference proceedings, and Google scholar. STUDY ELIGIBILITY CRITERIA Cohort or cross-sectional studies that rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 60 publications
(75 reference statements)
2
44
0
Order By: Relevance
“…The present investigation could have benefited from the addition of a cost analysis to determine the financial impact of different treatment modalities and admission rates based on the contingent results of biochemical tests after ultrasound. A recent systematic review and meta-analysis conducted by Conde-Agudelo et al on the phIGFBP-1 test, which reviewed 18 independent studies reporting the performance of phIGFBP-1 for predicting imminent spontaneous preterm birth within 7 days of presentation, concluded that there was insufficient evidence to recommend the routine clinical use of the phIGFBP-1 test in women with symptoms of preterm labor [22].…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation could have benefited from the addition of a cost analysis to determine the financial impact of different treatment modalities and admission rates based on the contingent results of biochemical tests after ultrasound. A recent systematic review and meta-analysis conducted by Conde-Agudelo et al on the phIGFBP-1 test, which reviewed 18 independent studies reporting the performance of phIGFBP-1 for predicting imminent spontaneous preterm birth within 7 days of presentation, concluded that there was insufficient evidence to recommend the routine clinical use of the phIGFBP-1 test in women with symptoms of preterm labor [22].…”
Section: Discussionmentioning
confidence: 99%
“…An immunochromatography‐based dipstick test is used to obtain the result within 5 minutes. The test reported pooled sensitivity and specificity in some studies . Among women with a singleton gestation and 30 mm cervical length, a positive cervical phIGFBP‐1 test (summary likelihood ratio of 5.5) increased the pretest probability of delivery within 7 days of testing from 17.8% to 54.4%, whereas a negative test result (summary likelihood ratio of 0.3) decreased the risk to 6.1%.…”
Section: Prediction Of Ptb In Symptomatic Women With Intact Membranesmentioning
confidence: 99%
“…phIGFBP-1 is produced by the placental decidual cells and thought to be released into the cervical vaginal fluid after tissue damage to the choriodecidual interface. 24 A qualitative test, either positive or negative, is measured from a vaginal swab taken with a speculum between 22 and 36 weeks of gestation. An immunochromatographybased dipstick test is used to obtain the result within 5 minutes.…”
Section: Prediction Of Ptb In Symptomatic Women With Intact Membranesmentioning
confidence: 99%
“…admission to the hospital, administration of steroids, transfer to a tertiary care center, etc.). This has been the basis for the evaluation of cervical length [4256], fetal fibronectin [5775], alpha-macroglobulin-1 [7679], insulin-like growth factor binding protein-1 [8089], and the concentration of inflammatory mediators in the amniotic fluid [90–116] and cervicovaginal fluid [88, 108, 117126] in patients presenting with increased uterine contractility or suspected preterm labor.…”
Section: Introductionmentioning
confidence: 99%